American Brain Tumor Association Young Investigator Award 198 Circulating Tumor Cells in Patients With Glioblastoma. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Nahed, Brian V.; Sullivan, James P.; Madden, Marissa W.; Oliveira, Samantha M.; Chi, Andrew S.; Springer, Simeon; Wakimoto, Hiro; Bhere, Deepak; Shah, Ajay; Spuhler, Phil; Batchelor, Tracy; Louis, David N.; et al.
Abstract: INTRODUCTION: Glioblastoma (GBM) is characterized by necrosis, angiogenesis, and inevitable recurrence. Despite its aggressiveness, GBM rarely forms extracranial metastases, suggesting impediments in vascular invasion, survival in circulation or implantation. Advances in microfluidics have successfully identified circulating tumor cells (CTCs) in lung, prostate, and breast cancer patients. Using a novel CTC microfluidic device, we hypothesize that GBM patients have CTCs, which can be captured, quantified, and analyzed for molecular and genetic markers. METHODS: We developed a microfluidic device (CTC-iChip) capable of capturing CTCs from whole blood via immunomagnetic depletion of hematopoietic blood cells. Using GBM-specific antibodies, we validated our CTC-iChip using GBM cell lines spiked into healthy donor blood. After successfully establishing our device, we evaluated venous blood samples (10 mL) from 6 healthy donors and 33 GBM patients preoperatively and postoperatively including chemotherapy and radiation therapy. CTCs were stained with a cocktail of GBM-specific antibodies and scanned by automated fluorescence microscopy. CTCs and their matched pathological specimens from surgery were further analyzed by Fluorescence in-Situ Hybridization (FISH). RESULTS: CTCs were detectable in at least 1 blood sample in 14/33 (42%) GBM patients. Patients with progressive disease harbored a median 11.8 CTCs per mL (mean 13.6 ± 10.7) compared to 2.1 CTCs per ml (mean: 4.0 ± 2.7) in patients with stable disease. CTC detection was significantly associated with disease progression ( P -value: .03), but not with other clinical variables such as disease location, extent of resection, or genotype. Fluorescence in situ hybridization analysis of CTCs from epidermal growth factor receptor-amplified and Chr7-polysomy GBM patients revealed 30/36 (83.3%) CTCs harbored concordant molecular aberrations. CONCLUSION: We identify the first evidence of CTCs in the peripheral blood of GBM patients. CTC frequency often varies during the course of therapy and is correlated with disease progression. Further studies are needed to define this novel discovery and its potential role in the care of GBM patients.